Predicting the characteristics of a C2B6 monolayer with ultrahigh carrier mobility - Xu, Ping; Zhu, Zhengyang; Zheng, Ruxin; Sun, Qingyun; Ma, Zhen; Mu, Weihua; Cui, Zhen (Frontiers in Chemistry, 2024)
Two-dimensional materials have excellent electronic and optical properties, suggesting absolute advantages in nanodevices. In this work, a new two-dimensional material with a puckered structure, a C2B6 monolayer, is proposed. The material presents dynamic and thermal stability calculated by first-principle simulations. Interestingly, the C2B6 monolayer possesses semiconductor behavior with an ultra-narrow bandgap of approximately 0.671 eV by HSE06 functional. Meanwhile, the hole in the C2B6 monolayer shows ultrahigh mobility at approximately 6,342 cm2⋅V−1⋅s−1 in decent transport directions, which is larger than traditional transition metal dichalcogenides materials. More importantly, the pronounced anisotropy of mobility of the electrons and holes can separate the photogenerated charges, suggesting the applications for photocatalytic, photovoltaic and optical and cold chain electronic devices. Then, the novel properties of the light absorption characteristic are obtained, and the anisotropic photocurrent implies the C2B6 monolayer can be used as a potential photoelectric device. Our results provide theoretical guidance for the design and application of two-dimensional materials.